ANALISIS KESESUAIAN MATERI BUKU TEKS SISWA KELAS IV SD/MI TEMA PEDULI TERHADAPMAKHLUK HIDUP TERBITAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN DENGAN KURIKULUM 2013 - Khairil Anwar,; Abdur Rahim, (JOEL: Journal of Educational and Language Research, 2022)
The purpose of the feasibility analysis on the contents of the fourth-grade elementary school/MI student textbooks with the theme of Caring for Living Creatures in the 2013 curriculum published by the Ministry of Education and Culture was to determine the accuracy and suitability of student textbooks based on KI and KD. This analysis was motivated by the limited time in the preparation of textbooks as well as textbooks as the main teaching material. Therefore, it was necessary to analyze the 2013 curriculum textbooks. As revised editions, these books need to be evaluated to produce more appropriate books. The method in this writing used a qualitative approach. The type of writing used was the writing of document analysis (documentary analysis) or content analysis. This writing was conducted to determine the condition of the fourth-grade elementary school/MI student textbooks on the theme of Caring for Living Creatures and their compatibility with K-13. This was carried out as an effort to improve the quality of textbooks for fourth-grade elementary school/MI students with the theme of Caring for Living Creatures used by educators and fourth-grade students of elementary school /MI. In this paper, the documentation guidelines used were based on the spiritual dimension, social dimension, knowledge dimension, and skill dimension set by BSNP. Furthermore, the data collection technique used was the scoring technique. This technique was carried out by putting a checklist on the scoring sheet according to the assessment criteria. The next data analysis technique was to calculate the percentage of each aspect. The results of the analysis of the fourth-grade elementary school/MI student textbooks with the theme Caring for Living Creatures in the 2013 curriculum published by the Ministry of Education and Culture are as follows: (1) The feasibility of the spiritual dimension is 57% or in the less feasible category. (2) The feasibility of the social dimension is 99% or in the very feasible category. (3) The feasibility of the knowledge dimension is 80% or in the very feasible category. (4) The feasibility of the skill dimension is 83.33% or in the very feasible category.